KONSEP INCEP DALAM PENYAJIAN KOTEKAN GAMELAN GONG KEBYAR - Adi, Komang Kusuma; Christiana, Whayan (Paraguna, 2023)
Balinese gamelan music has its own aesthetic dimensions for the group of performers and listeners. However, it can be realized that achieving a beautiful aesthetic dish is not an easy matter. Especially for those who are new to, studying, or who do not own cultural products. This research tries to investigate further the concept of incep which is one of the references for the aesthetic value of Balinese gamelan offerings, especially Gong Kebyar. The aim is to find components that form concepts that can be used as guidelines in the art inheritance system and its performances. The author uses a qualitative research model, with a textual ethnomusicological approach and the working theory popularized by Rahayu Supanggah. Based on the research carried out, it can be seen that the concept of incep is related to the value of a dish which includes instrument blows that sound clear, precise and compact. The components that form the concept consist of ngatih, celang, and maketekan. These three components have sub-requisites to achieve the desired value. Because if it cannot be fulfilled then it is certain that there will be sounds that are less clean or uncomfortable to hear in the ear. On the other hand, if everything can be fulfilled, then surely the percussion performance can achieve the aesthetic value of the incep performance